Analisis Komponen Fisik Terhadap Kemampuan Menggiring Bola Permainan Sepakbola Sma Negeri 11 Makassar - Karim, Achmad; Hasbillah, Muhammad (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
This research is a descriptive study using a correlational research design. The population is all students of SMA Negeri 11 Makassar. The sample used was 30 students. The sampling technique was simple random sampling. The data analysis technique used is descriptive analysis, pearson product moment correlation coefficient analysis (r), and the results of multiple correlation analysis (R) at the significant level Î± = 0.05. The results showed that; (1) There is a significant relationship between ankle coordination and dribbling ability in soccer game for student of SMA Negeri 11 Makassar, with a value of r = 0,561 (Ï<Î± = 0.05); (2) There is a significant relationship between balance and dribbling ability in soccer game for student of SMA Negeri 11 Makassar, with a value of r = 0,603 (Ï<Î± = 0.05); (3) There is a significant relationship between leg muscle strenght and dribbling ability in soccer game for student of SMA Negeri 11 Makassar, with a value of r = 0,728 (Ï<Î± = 0.05); (4) There is a significant relationship simultaneously between ankle coordination, balance, leg muscle strenght and dribbling ability in soccer game for student of SMA Negeri 11 Makassar, with a determinant coefficient value (R2) = 0,733 or 73,3%.